KNOWLEDGE, ATTITUDE AND PRACTICES OF PAKISTANI WOMEN REGARDING BREAST CANCER: Breast Cancer - Sultana, Riffat; Tahir, Sadia; Ali, Dilshad (Pakistan Armed Forces Medical Journal, 2018)
Objective: To assess the knowledge, attitude and practices of Pakistani women about breast cancer.Study Design: Descriptive cross-sectional study.Place and Duration of Study: Pak Emirates Military Hospital Rawalpindi, from Sep 2012 to Feb 2013.Material and Methods: Two hundred adult female patients and their accompanying attendants were randomlyselected (Those with breast complaints were excluded) in outpatient department of military hospitals andwere interviewed. In order to gather data patients were asked to reply through a questionnaire along with theirdemographic profile structure questionnaire, comprising of 28 questions (included both open and closed ended),was used to collect data which was analyzed in the end with the help of SPSS version 15.Results: Mean age of participants was 37.5 ± 7.5 years. Majority were married (87%), housewives (89%) withaverage family income of Rupees 15000 (53%). Majority 94% (n=188) had heard about breast cancer. Questionsregarding knowledge showed that participants awareness about relationship of breast cancer with obesity,smoking and increasing age was more than 50%. Up to 70% women had knowledge of breast lump as mainsymptom of breast cancer. Knowledge regarding diagnostic modalities was very poor. Only 16% knew aboutFNAC/Biopsy and 7.5% about mammography. A large majority (90%) showed positive attitude and were readyto see a doctor immediately in case they felt a lump in breast but practices of breast self-examination were poor(39%).Conclusion: It was concluded that knowledge of most respondents was limited, practices were poor, but attitudetowards breast cancer was positive. Lack of education, socio-cultural taboos and getting information from wrongsources surfaced as leading reasons of unawareness.